Introducing bi-directional participatory place branding: a theoretical model with multi-stakeholder perspectives. Issue 1 (2nd April 2021) - Jain, Varsha; Shroff, Preeti; Merchant, Altaf; Bezbaruah, Subhalakshmi
Abstract : Purpose: A place brand is a culmination of its exclusive history, people and traditions that affect customer and community experiences. Place branding has become increasingly important for collective heritage brand strategy, as stakeholders undertake efforts to create an aura of a distinctive geographic location. Though place branding has received considerable scholarly attention, there is a lacuna: the role of residents as co-creators of a place and its heritage. Accordingly, this paper aims to develop a "bi-directional participatory place branding" model by applying the stimulus–organism–response approach grounded theory. Design/methodology/approach: A grounded theory approach with multi-sited ethnography, personal interviews (with residents and city leaders) and observational techniques were adopted in a UNESCO world heritage city of India, Ahmedabad. Findings: The findings indicate that the people (residents) aspect of place branding is associated with their life stories, past experiences, feelings and aspirations. However, the place acts as a nostalgia enabler, disseminating symbolic and heritage metaphors to residents and visitors as place brand ambassadors. When the place and people components are perceived positively, residents participate involve themselves with the place and thus, in turn, become the place ambassadors. Originality/value: No prior studies have analyzed the association between residents, the place where they reside and the resultant behavior toward the place. The unique contribution is the bi-directional participatory place branding model, especially involving a UNESCO world heritage city rather than solely a site.